2022
DOI: 10.1021/acs.jpcb.1c10750
|View full text |Cite
|
Sign up to set email alerts
|

From Protein Design to the Energy Landscape of a Cold Unfolding Protein

Abstract: Understanding protein folding is crucial for protein sciences. The conformational spaces and energy landscapes of cold (unfolded) protein states, as well as the associated transitions, are hardly explored. Furthermore, it is not known how structure relates to the cooperativity of cold transitions, if cold and heat unfolded states are thermodynamically similar, and if cold states play important roles for protein function. We created the cold unfolding 4-helix bundle DCUB1 with a de novo designed bipartite hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 110 publications
0
3
0
Order By: Relevance
“…The protein concentration was set at 5 μM in 2 mL of solution in a buffer of 20 mM Na 2 HPO 4 /NaH 2 PO 4 (pH 7.0) with 50 mM NaCl. In addition to the emission spectra, the center of spectral mass (CM) was calculated using eq : , CM = i λ i F i i F i where F i is the emission in the wavelength λ i .…”
Section: Methodsmentioning
confidence: 99%
“…The protein concentration was set at 5 μM in 2 mL of solution in a buffer of 20 mM Na 2 HPO 4 /NaH 2 PO 4 (pH 7.0) with 50 mM NaCl. In addition to the emission spectra, the center of spectral mass (CM) was calculated using eq : , CM = i λ i F i i F i where F i is the emission in the wavelength λ i .…”
Section: Methodsmentioning
confidence: 99%
“…We have recently shown that protein design is poised to play a key role to explore protein cold unfolding energy landscapes, the mechanisms of cold unfolding, and to robustly test related theories . Specifically, we designed cold unfolding 4-helix bundles with de novo designed bipartite hydrophilic/hydrophobic cores featuring hydrogen-bond networks to study the relative importance of hydrophobic versus hydrophilic protein–water interactions for cold unfolding.…”
Section: Discussionmentioning
confidence: 99%
“…9 We have recently shown that protein design is poised to play a key role to explore protein cold unfolding energy landscapes, the mechanisms of cold unfolding, and to robustly test related theories. 38 Specifically, we designed cold unfolding 4-helix bundles with de novo designed bipartite hydrophilic/hydrophobic cores featuring hydrogen-bond networks to study the relative importance of hydrophobic versus hydrophilic protein−water interactions for cold unfolding. Our strategy presented here to design inside-out zinc-binding sites offers new opportunities for the design of cold unfolding proteins with zinc coordination sites representing the hydrophilic segment that potentially accommodates intruding waters during the onset of cold unfolding.…”
Section: ■ Discussionmentioning
confidence: 99%